Work-Life Balance and Burnout as Factor Influencing Nurse Performance at Cirebon Port General Hospital - Jihan Dwinda Rostianti; Muhamad Rafli Febrian; Noveria Susijawati; Sunimah Sunimah (Rescollacom (Research Collaborations Community), 2025)
The purpose of this study is to ascertain how burnout and work-life balance affect nurse performance at Cirebon Port Hospital. This study's methodology is quantitative, and its study population consists of 117 hospital-employed nurses. Using a saturated sample approach, all nurses participated in the survey. The survey with a Likert scale from 1 to 5 was used to gather data, and the statistical program SPSS was used for analysis. Multiple linear regression analysis was employed to examine the impact of burnout and work life balance on nurse performance, as well as to validate the validity, reliability, and classical assumption tests. Based on the findings, nurse performance is positively and significantly impacted by work-life balance. Burnout affects nurse performance negatively, however the effect is not statistically significant.